Pollination in the Middle East - Monks, Joseph (2020)
Pollination networks have traditionally been seen as static, specialised systems. This view has supported the concept of pollination syndromes; the idea that plants evolve particular traits that attract specific pollinator types. However, this view has been challenged in the last few decades as a community level approach has revealed plants are visited by a wide range of taxa. Conversely, xeric environments are rich in oligolectic bee species, suggesting specialism is dominant in this habitat type. This thesis used the Hajar Mountains in Oman as a study site to investigate how visitation networks change temporally and spatially. Specialism appears to be the governing process across all types of flower visitor, not just bee species. However, when a temporal approach is taken, species replacement was extremely high, indicating a constant fluctuation in the composition of the networks in this mountain range, which like in other studies challenges the notions regarding floral syndromes. Species distribution models show a degree of homogenisation in bee communities across the Arabian Peninsula. This contrasts at more local level as seen in the Hajar Mountains. Further studies are now needed to DNA barcode pollen loads from bee specimens collected during the study and region as a whole. This would allow a clearer understanding of network dynamics and help clarify whether the observed specialism seen in this study reflects evolutionary specialism or simply floral constancy.